Empirical models challenging biblical criticism - Person, Raymond F.; Rezetko, Robert (Ancient Israel and its literature, 2016)
"Empirical models based on ancient Near Eastern literature and variations between different textual traditions have been used to lend credibility to the identification of the sources behind biblical literature and the different editorial layers. In this volume, empirical models are used to critique the exaggerated results of identifying sources and editorial layers by demonstrating that, even though much of ancient literature had such complex literary histories, our methods are often inadequate for the task of precisely identifying sources and editorial layers"--